Principles of Customer Due Diligence (CDD) in the Pattern of Channeling Financing Cooperation by Sharia Peer to Peer Lending Banks (BPRS) through Sharia Peer to Peer Lending. - Rosida, Fitriatur; Susmayanti, Riana; Dian, Novitasari (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Problems regarding the Customer Due Diligence (CDD) Principle in the Pattern of Financing Cooperation by Channeling by Sharia People's Economic Banks (BPRS) through Sharia Peer to Peer Lending. The problem is raised from the background of the development of Islamic economics or called sharia economics in Indonesia which is growing rapidly. The community is enthusiastic about the very high growth of Islamic economic practices, it can be seen that there are many establishments of financial institutions with sharia principles, one of which is the Sharia People's Economic Bank, hereinafter referred to as BPRS. Sharia BPR is one of the financial institutions which means that in this case carrying out business activities based on sharia principles has the function of collecting public funds (funding) and channeling public funds (lending / financing). The research method used is normative legal research using statutory and conceptual approach methods. using primary, secondary, and tertiary legal materials analyzed using grammatical and systematic interpretation of provisions relating to sharia peer to peer lending. The results of this study reveal that in the Islamic financing channeling scheme, there are two main types of interrelated agreements: a cooperation agreement between BPR Syariah and Islamic peer to peer lending based on a wakalah (power of attorney) contract, and a financing agreement between Islamic peer to peer lending and customers using a murabahah or musyarakah mutanaqisah contract.